Design and Analysis of Novel Folded Optical Multi-Pass Cell - Cheng, Gang; Cao, Ya-Nan; Tian, Xing; Chen, Jia-Jin; Wang, Jing-Jing (Frontiers in Physics, 2022)
A novel folded multi-pass cell consisting of three non-coaxial mirrors (spherical mirror or plane mirror) is proposed for laser spectroscopy. Three mirrors of the folded multi-pass cell can arrange in V-shape to form a stable non-coaxial multi-pass cell. Furthermore, in order to research the stability of the multi-pass cell under off-axis mirror’s astigmatism circumstance, an equivalent coaxial multi-pass cell and modified ABCD matrix model for the spot pattern of the folded multi-pass cell is proposed, by which a series of the detailed numerical calculations were implemented to analyze the optical path length of the multi-pass cell. Many spot patterns obtained with a high fill factor improve the utilization efficiency of the surface of the mirror and produce a longer total optical path length. The several typical types of the folded multi-pass cells consisting of the different mirrors and base length were selected to demonstrate the cell’s self-consistent condition and power for a longer-optical path length. Three effective optical path length s of 49.6 m, 97.6 m and 173.6 m were obtained, respectively.